Corrosion-resistant galvanized steel pipe and preparation process thereof

By synthesizing functionalized carbon spot corrosion inhibitors and modified boron nitride nanosheets, combined with modified zinc oxide nanoparticles, a passivation liquid is prepared, which solves the problem that the hot-dip galvanized layer is prone to accumulate white rust in the atmosphere, and significantly improves the corrosion resistance of galvanized steel pipes.

CN119736615AActive Publication Date: 2025-04-01江苏智润管业有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510258590.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-01
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

The hot-dip galvanized layer is prone to accumulation of white rust in the atmosphere, affecting the appearance and quality of the product, and it is difficult to maintain excellent performance under various environmental conditions.

Method used

The amino-modified carbon spot corrosion inhibitor was synthesized by hydrothermal method, and the dopamine monomer was connected to its surface through the EDC/NHS coupling reaction to prepare a functional carbon spot corrosion inhibitor. Then, it is used as an intercalation agent to modify and peel off boron nitride to prepare intercalation modified boron nitride nanosheets. Finally, modified zinc oxide nanoparticles were combined with composite boron nitride nanosheets to prepare a passivation liquid for passivation treatment of galvanized steel pipes.

Benefits of technology

It significantly improves the long-term corrosion resistance of the passivation liquid, increases the distance between boron nitride sheets, improves dispersion, extends the diffusion path of corrosive media, and forms a stable complex through the specific interaction of dopamine, blocks the contact between the steel surface and the corrosive media, and significantly improves the corrosion resistance of galvanized steel pipes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of galvanized steel pipes, and discloses a corrosion-resistant galvanized steel pipe and a preparation process thereof. The functionalized carbon dot corrosion inhibitor is prepared by synthesizing an amino-modified carbon dot corrosion inhibitor through a hydrothermal method and then connecting a dopamine monomer to the surface of the amino-modified carbon dot corrosion inhibitor in a covalent bond form through a coupling reaction. And finally, modifying and stripping boron nitride by using the modified boron nitride nanosheets as an intercalation agent to prepare intercalation modified boron nitride nanosheets. The preparation method comprises the following steps: modifying nano-zinc oxide particles by using dopamine, and grafting KH590 on the surface of the nano-zinc oxide particles by using a pi-pi accumulation effect of catechol groups on the polydopamine and aromatic rings on a corrosion inhibitor and using a large number of active functional groups on the polydopamine, so as to prepare the modified zinc oxide nano-particles. And finally, carrying out dehydration condensation reaction, and loading on the intercalation modified boron nitride nanosheet, so as to prepare the composite boron nitride nanosheet. The corrosion-resistant passivating agent is used as a main component of a passivating agent to form a layer of passivating film on the galvanized steel pipe, and finally the corrosion-resistant galvanized steel pipe is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of galvanized steel pipes, in particular to a corrosion-resistant galvanized steel pipe and a preparation process thereof. Background Art

[0002] Hot-dip galvanizing technology is often used to protect steel substrates from corrosion. However, in the atmosphere, white rust easily accumulates on the surface of the hot-dip galvanized layer, which has an adverse effect on the appearance and quality of hot-dip galvanized products. In order to solve this problem, hot-dip galvanizing surface passivation treatment is usually used to effectively protect the hot-dip galvanized layer from corrosion; through this comprehensive protective measure, hot-dip galvanized products can not only form a solid protective layer on the surface to effectively resist external corrosion factors, but also maintain their appearance and quality, ensuring that they can maintain excellent performance under various environmental conditions. These measures are essential to improving the reliability and durability of hot-dip galvanized products.

[0003] Therefore, it is of great significance to invent a corrosion-resistant galvanized steel pipe and a preparation process thereof. Summary of the invention

[0004] The object of the present invention is to provide a corrosion-resistant galvanized steel pipe and a preparation process thereof to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation process of a corrosion-resistant galvanized steel pipe comprises the following steps: S1: Glucose, anhydrous citric acid, and 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole are added to deionized water, heated to 180-185° C. for reaction for 4-4.5 hours, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: ultrasonically dispersing the carbon dot corrosion inhibitor in deionized water, adjusting the pH to 6-6.5; adding 1-ethyl-carbodiimide hydrochloride solution and N-hydroxysuccinimide solution for activation, adding dopamine, passing oxygen to remove dissolved oxygen in the reaction system, stirring the reaction for 3-3.5 hours, purifying, and vacuum drying to obtain a modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing the modified carbon dot corrosion inhibitor and hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: ultrasonically dispersing zinc oxide nanoparticles in a Tris-HCl solution, adding dopamine and a corrosion inhibitor solution, reacting at room temperature for 24-26 hours, purifying, and vacuum drying to obtain modified zinc oxide nanoparticles A; ultrasonically dispersing modified zinc oxide nanoparticles A in N,N-dimethylformamide, adding KH590, heating to 80-85°C and reacting for 3-4 hours to obtain modified zinc oxide nanoparticles B; S5: ultrasonically dispersing the intercalated modified boron nitride nanosheets in N,N-dimethylformamide, adding modified zinc oxide nanoparticles B and ultrasonically dispersing them uniformly, heating to 105-107° C. for reaction for 5-6 hours, purifying, and vacuum drying to obtain composite boron nitride nanosheets; S6: Dissolve tannic acid in deionized water, add fatty alcohol polyoxyethylene ether, hydroxyethylidene diphosphonic acid, and emulsifier and stir evenly, add aqueous acrylic resin solution and stir evenly, add composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30-32°C, immerse the galvanized steel pipe in the passivation solution for 20-30s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0006] Furthermore, in the carbon dot corrosion inhibitor, the mass ratio of glucose: anhydrous citric acid: 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole is 1:1:(0.5-1.2); Furthermore, in the modified carbon dot sustained-release agent, the mass ratio of carbon dot corrosion inhibitor to dopamine is 80:(60-75.9); the concentration of the 1-ethyl-carbodiimide hydrochloride solution is 0.1 mol / L; the concentration of the N-hydroxysuccinimide solution is 0.1 mol / L; Furthermore, in the intercalated modified boron nitride nanosheets, the mass ratio of modified carbon dot corrosion inhibitor: hexagonal boron nitride is (0.25-0.5):0.2; Furthermore, in the modified zinc oxide nanoparticles A, the mass ratio of zinc oxide nanoparticles: dopamine: corrosion inhibitor in the corrosion inhibitor solution is 2: (2-3): (8-9); the concentration of the Tris-HCl solution is 10 mM, and the pH is 8.5; the concentration of the corrosion inhibitor solution is 160 mg / mL, and the corrosion inhibitor is any one of benzimidazole and benzotriazole; Furthermore, in the modified zinc oxide nanoparticles B, the mass ratio of modified zinc oxide nanoparticles A:KH590 is (4-5):(1.6-3); Furthermore, in the composite boron nitride nanosheets, the mass ratio of intercalated modified boron nitride nanosheets: modified zinc oxide nanoparticles B is 3:(1-2); Furthermore, the proportions of the components in the passivation solution, by mass, are 0.5-0.8 parts of tannic acid, 0.15-0.2 parts of fatty alcohol polyoxyethylene ether, 0.15-0.2 parts of hydroxyethylidene diphosphonic acid, 0.15-0.2 parts of emulsifier, 40-50 parts of aqueous acrylic resin solution, and 1-5 parts of composite boron nitride nanosheets.

[0007] Furthermore, the emulsifier is OP-10.

[0008] Furthermore, the method for preparing the galvanized steel pipe comprises the following steps: The steel pipe substrate is sequentially subjected to degreasing, water washing, pickling, and water washing pretreatment; the pretreated steel pipe is placed in a chemical plating solution, heated to 50-55°C and subjected to constant temperature chemical galvanizing for 10-15 minutes to obtain a galvanized steel pipe; Furthermore, the solution used in the degreasing step is a 10wt% sodium hydroxide solution, and the solution used in the pickling step is a 16wt% hydrochloric acid solution; the chemical plating solution is composed of 30-40g / L zinc sulfate heptahydrate and 140-150g / L potassium pyrophosphate trihydrate; the thickness of the galvanized layer of the galvanized steel pipe is 8-9μm.

[0009] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention synthesizes an amino-modified carbon dot corrosion inhibitor by a hydrothermal method, and then uses an EDC / NHS coupling reaction to connect a dopamine monomer to its surface in the form of a covalent bond to prepare a functionalized carbon dot corrosion inhibitor. Finally, it is used as an intercalation agent to modify and exfoliate boron nitride to prepare an intercalated modified boron nitride nanosheet. The doping of nanocomposite fillers significantly improves the long-term corrosion resistance of the passivation solution. The functionalized carbon dot corrosion inhibitor has a dual role as an intercalation agent: on the one hand, it increases the interlayer distance of the boron nitride sheets, significantly improves the dispersibility of the boron nitride nanosheets, and the exfoliated boron nitride nanosheets exert a maze effect, effectively extending the diffusion path of the corrosive medium and blocking the inherent defects inside the coating; on the other hand, the dopamine catechol residues on the surface of the intercalation agent can react with Fe 3+ or Fe 2+ Specific interactions form stable complexes, blocking the contact between the steel surface and the corrosive medium, greatly improving the corrosion resistance of the passivation layer.

[0010] The invention uses zinc oxide nanoparticles as templates, modifies the nanoparticles by coating a layer of polydopamine on the surface of the nanoparticles, utilizes the II-II stacking effect between the catechol group on the polydopamine and the aromatic ring on the corrosion inhibitor, loads the polydopamine as the anchor point of the corrosion inhibitor on the polydopamine, and then utilizes a large number of active functional groups on the polydopamine to graft KH590 on the surface of the polydopamine-modified nano zinc oxide particles loaded with the corrosion inhibitor through Michael addition reaction to prepare modified zinc oxide nanoparticles, and finally loads the nanoparticles on the intercalation modified boron nitride nanosheets through the dehydration condensation reaction of a silane coupling agent to prepare composite boron nitride nanosheets; utilizes polydopamine to chelate Zn 2+ The characteristics of the metal chelate further enhance the shielding effect of the metal chelate on the surface of the galvanized steel pipe and further enhance the corrosion resistance of the passivation layer.

[0011] The functionalized carbon dots corrosion inhibitor and modified zinc oxide nanoparticles are loaded into boron nitride nanosheets through intercalation and condensation, which greatly improves the corrosion resistance application range of the passivation solution. On the one hand, when the pH of the corrosive medium is neutral, the functionalized carbon dots corrosion inhibitor as an intercalation agent can maximally interact with Fe 3+ or Fe 2+ A specific interaction occurs to form a stable complex; on the other hand, the prepared modified zinc oxide nanoparticles utilize the pH response behavior of polydopamine to achieve a sustained release effect. When the pH is acidic, due to the presence of amino groups on polydopamine and the corrosion inhibitor, the positive electrical repulsion between polydopamine and the corrosion inhibitor causes a large amount of corrosion inhibitor to be released, providing corrosion inhibition properties for the galvanized steel pipe; the combination of the two greatly broadens the application range of galvanized steel pipes and provides excellent corrosion protection for steel pipes. DETAILED DESCRIPTION

[0012] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0013] In the following examples, hexagonal boron nitride has a particle size of 5-10 μm and is purchased from Beijing Puxitang Biotechnology Co., Ltd.; zinc oxide nanoparticles have an α-type crystal form and a particle size of 20 nm and are purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; the steel pipe matrix model is Q235 and is purchased from Wuxi Chuanyue Steel Co., Ltd.; the remaining raw materials are commercially available.

[0014] The method for preparing the galvanized steel pipe comprises the following steps: The steel pipe substrate was degreased with 10wt% sodium hydroxide solution, washed with deionized water, pickled with 16wt% hydrochloric acid solution, and pretreated with deionized water; the pretreated steel pipe was placed in a chemical plating solution composed of 40g / L zinc sulfate heptahydrate and 150g / L potassium pyrophosphate trihydrate, heated to 50°C for constant temperature chemical galvanizing for 10 minutes to obtain a galvanized steel pipe with a zinc coating thickness of 8μm.

[0015] Example 1: A process for preparing a corrosion-resistant galvanized steel pipe: S1: 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole were added into deionized water, heated to 180° C. for reaction for 4 h, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 60 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 2.5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: 2 g of zinc oxide nanoparticles were ultrasonically dispersed in 10 mM Tris-HCl solution, 2 g of dopamine and 8 g of benzotriazole were added, the mixture was reacted at room temperature for 24 h, purified, and vacuum dried to obtain modified zinc oxide nanoparticles A; 4 g of modified zinc oxide nanoparticles A were ultrasonically dispersed in N,N-dimethylformamide, 1.6 g of KH590 was added, and the mixture was heated to 80 °C for 3 h to obtain modified zinc oxide nanoparticles B; S5: ultrasonically disperse 3 g of intercalated modified boron nitride nanosheets in N,N-dimethylformamide, add 1 g of modified zinc oxide nanoparticles B and ultrasonically disperse them uniformly, heat to 105°C for reaction for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S6: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethyl diphosphonic acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 1g of composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0016] Example 2: A process for preparing a corrosion-resistant galvanized steel pipe: S1: 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole were added into deionized water, heated to 180° C. for reaction for 4 h, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 75.9 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 2.5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: 2 g of zinc oxide nanoparticles were ultrasonically dispersed in 10 mM Tris-HCl solution, 2 g of dopamine and 8 g of benzotriazole were added, the mixture was reacted at room temperature for 24 h, purified, and vacuum dried to obtain modified zinc oxide nanoparticles A; 4 g of modified zinc oxide nanoparticles A were ultrasonically dispersed in N,N-dimethylformamide, 1.6 g of KH590 was added, and the mixture was heated to 80 °C for 3 h to obtain modified zinc oxide nanoparticles B; S5: ultrasonically disperse 3 g of intercalated modified boron nitride nanosheets in N,N-dimethylformamide, add 1 g of modified zinc oxide nanoparticles B and ultrasonically disperse them uniformly, heat to 105°C for reaction for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S6: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethyl diphosphonic acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 1g of composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0017] Example 3: A process for preparing a corrosion-resistant galvanized steel pipe: S1: 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole were added into deionized water, heated to 180° C. for reaction for 4 h, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 60 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: 2 g of zinc oxide nanoparticles were ultrasonically dispersed in 10 mM Tris-HCl solution, 2 g of dopamine and 8 g of benzotriazole were added, the mixture was reacted at room temperature for 24 h, purified, and vacuum dried to obtain modified zinc oxide nanoparticles A; 4 g of modified zinc oxide nanoparticles A were ultrasonically dispersed in N,N-dimethylformamide, 1.6 g of KH590 was added, and the mixture was heated to 80 °C for 3 h to obtain modified zinc oxide nanoparticles B; S5: ultrasonically disperse 3 g of intercalated modified boron nitride nanosheets in N,N-dimethylformamide, add 1 g of modified zinc oxide nanoparticles B and ultrasonically disperse them uniformly, heat to 105°C for reaction for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S6: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethyl diphosphonic acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 1g of composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0018] Example 4: A process for preparing a corrosion-resistant galvanized steel pipe: S1: 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole were added into deionized water, heated to 180° C. for reaction for 4 h, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 75.9 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: 2 g of zinc oxide nanoparticles were ultrasonically dispersed in 10 mM Tris-HCl solution, 3 g of dopamine and 9 g of benzotriazole were added, the mixture was reacted at room temperature for 24 h, purified, and vacuum dried to obtain modified zinc oxide nanoparticles A; 4 g of modified zinc oxide nanoparticles A were ultrasonically dispersed in N,N-dimethylformamide, 3 g of KH590 was added, and the mixture was heated to 80 °C for 3 h to obtain modified zinc oxide nanoparticles B; S5: ultrasonically disperse 3 g of intercalated modified boron nitride nanosheets in N,N-dimethylformamide, add 1 g of modified zinc oxide nanoparticles B and ultrasonically disperse them uniformly, heat to 105°C for reaction for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S6: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethyl diphosphonic acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 1g of composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0019] Example 5: A process for preparing a corrosion-resistant galvanized steel pipe: S1: Add 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole into deionized water, heat to 180° C. for reaction for 4 h, cool, filter under reduced pressure, purify, and freeze-dry to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 75.9 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: 2 g of zinc oxide nanoparticles were ultrasonically dispersed in 10 mM Tris-HCl solution, 3 g of dopamine and 9 g of benzotriazole were added, the mixture was reacted at room temperature for 24 h, purified, and vacuum dried to obtain modified zinc oxide nanoparticles A; 4 g of modified zinc oxide nanoparticles A were ultrasonically dispersed in N,N-dimethylformamide, 3 g of KH590 was added, and the mixture was heated to 80 °C for 3 h to obtain modified zinc oxide nanoparticles B; S5: ultrasonically disperse 3 g of intercalated modified boron nitride nanosheets in N,N-dimethylformamide, add 2 g of modified zinc oxide nanoparticles B and ultrasonically disperse them uniformly, heat to 105°C for reaction for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S6: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethyl diphosphonic acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 1g of composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0020] Example 6: A process for preparing a corrosion-resistant galvanized steel pipe: S1: 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole were added into deionized water, heated to 180° C. for reaction for 4 h, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 75.9 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: 2 g of zinc oxide nanoparticles were ultrasonically dispersed in 10 mM Tris-HCl solution, 3 g of dopamine and 9 g of benzotriazole were added, the mixture was reacted at room temperature for 24 h, purified, and vacuum dried to obtain modified zinc oxide nanoparticles A; 4 g of modified zinc oxide nanoparticles A were ultrasonically dispersed in N,N-dimethylformamide, 3 g of KH590 was added, and the mixture was heated to 80 °C for 3 h to obtain modified zinc oxide nanoparticles B; S5: ultrasonically disperse 3 g of intercalated modified boron nitride nanosheets in N,N-dimethylformamide, add 2 g of modified zinc oxide nanoparticles B and ultrasonically disperse them uniformly, heat to 105°C for reaction for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S6: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethylidene diphosphoric acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 5g of composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0021] Comparative Example 1: A process for preparing a corrosion-resistant galvanized steel pipe: S1: Ultrasonic dispersion of 2 g zinc oxide nanoparticles in 10 mM Tris-HCl solution, addition of 2 g dopamine and 8 g benzotriazole, reaction at room temperature for 24 h, purification, vacuum drying, to obtain modified zinc oxide nanoparticles A; ultrasonic dispersion of 4 g modified zinc oxide nanoparticles A in N,N-dimethylformamide, addition of 1.6 g KH590, heating to 80 ° C for reaction for 3 h, to obtain modified zinc oxide nanoparticles B; S2: ultrasonically disperse 3 g of hexagonal boron nitride in N,N-dimethylformamide, add 1 g of modified zinc oxide nanoparticles B and ultrasonically disperse them evenly, heat to 105°C for reaction for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S3: Dissolve 0.5g tannic acid in deionized water, add 0.15g fatty alcohol polyoxyethylene ether, 0.15g hydroxyethyl diphosphonic acid, and 0.15g emulsifier OP-10 and stir evenly, add 40g aqueous acrylic resin solution and stir evenly, add 1g composite boron nitride and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0022] Comparative Example 2: A process for preparing a corrosion-resistant galvanized steel pipe: S1: 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole were added into deionized water, heated to 180° C. for reaction for 4 h, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 60 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 2.5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethyl diphosphonic acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 1g of intercalated modified boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0023] Comparative Example 3: A process for preparing a corrosion-resistant galvanized steel pipe: S1: 10 g of glucose, 10 g of anhydrous citric acid, and 8 g of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole were added into deionized water, heated to 180° C. for reaction for 4 h, cooled, filtered under reduced pressure, purified, and freeze-dried to obtain a carbon dot corrosion inhibitor; S2: 80 mg of carbon dot corrosion inhibitor was ultrasonically dispersed in deionized water, and the pH was adjusted to 6; 2 mL of 0.1 mol / L 1-ethyl-carbodiimide hydrochloride solution and 2 mL of 0.1 mol / L N-hydroxysuccinimide solution were added for activation, 60 mg of dopamine was added, and the dissolved oxygen in the reaction system was removed by oxygenation, and the reaction was stirred for 3 h, purified, and vacuum dried to obtain the modified carbon dot corrosion inhibitor; S3: ultrasonically dispersing 2.5 g of modified carbon dot corrosion inhibitor and 2 g of hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, filtering the supernatant under reduced pressure, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets; S4: 2 g of zinc oxide nanoparticles were ultrasonically dispersed in 10 mM Tris-HCl solution, 2 g of dopamine was added, the mixture was reacted at room temperature for 24 h, purified, and vacuum dried to obtain modified zinc oxide nanoparticles A; 4 g of modified zinc oxide nanoparticles A were ultrasonically dispersed in N,N-dimethylformamide, 1.6 g of KH590 was added, and the mixture was heated to 80 °C for 3 h to obtain modified zinc oxide nanoparticles B; S5: ultrasonically disperse 3 g of intercalated modified boron nitride nanosheets in N,N-dimethylformamide, add 1 g of modified zinc oxide nanoparticles B and 8 g of benzotriazole, ultrasonically disperse evenly, heat to 105°C for 5 h, purify, and vacuum dry to obtain composite boron nitride nanosheets; S6: Dissolve 0.5g of tannic acid in deionized water, add 0.15g of fatty alcohol polyoxyethylene ether, 0.15g of hydroxyethyl diphosphonic acid, and 0.15g of emulsifier OP-10 and stir evenly, add 40g of aqueous acrylic resin solution and stir evenly, add 1g of composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30°C, immerse the galvanized steel pipe in the passivation solution for 20s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe.

[0024] experiment: Copper sulfate drip test: The test is carried out according to the standard GB / T 2972-2016. The formula of copper sulfate solution is: copper sulfate 40g / L, sodium chloride 35g / L, hydrochloric acid 15mL / L. The corrosion resistance of the corrosion-resistant galvanized pass after passivation is measured by judging the time when the surface of the sample turns black.

[0025] Neutral salt spray test: Tested according to GB / T 1771-2007; the corrosive medium is 5wt% sodium chloride solution, the temperature is 35-37℃, the suitability is 95%, and the fogging volume is 2mL / (h·cm 2 ); evaluated according to standard GB6461-86.

[0026] Table 1 Copper sulfate drop neutral salt spray test data

[0027] Conclusion: The corrosion-resistant galvanized steel pipe prepared by the present invention has excellent corrosion resistance and excellent corrosion protection performance under neutral and acidic conditions. Comparative Example 1 does not prepare an intercalation agent, and Comparative Example 2 does not load modified zinc oxide nanoparticles, resulting in reduced corrosion resistance. Comparative Example 3 does not load the corrosion inhibitor on the polydopamine modified nanoparticles, resulting in reduced sustained release and reduced corrosion resistance.

[0028] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A process for preparing a corrosion-resistant galvanized steel pipe, characterized in that: The following steps are involved: S1: Ultrasonic dispersion of zinc oxide nanoparticles in Tris-HCl solution, adding dopamine and corrosion inhibitor solution, reacting at room temperature for 24-26 hours, purifying, and vacuum drying to obtain modified zinc oxide nanoparticles A; ultrasonic dispersion of modified zinc oxide nanoparticles A in N,N-dimethylformamide, adding KH590, heating to 80-85°C and reacting for 3-4 hours to obtain modified zinc oxide nanoparticles B; S2: ultrasonically dispersing the intercalated modified boron nitride nanosheets in N,N-dimethylformamide, adding modified zinc oxide nanoparticles B and ultrasonically dispersing them uniformly, heating to 105-107°C for reaction for 5-6h, purifying, and vacuum drying to obtain composite boron nitride nanosheets; S3: dissolve tannic acid in deionized water, add fatty alcohol polyoxyethylene ether, hydroxyethylidene diphosphonic acid, and emulsifier and stir evenly, add aqueous acrylic resin solution and stir evenly, add composite boron nitride nanosheets and stir evenly to obtain a passivation solution; preheat the passivation solution to 30-32°C, immerse the galvanized steel pipe in the passivation solution for 20-30s, take out, wash, and dry to obtain a corrosion-resistant galvanized steel pipe; The preparation method of the intercalated modified boron nitride nanosheets comprises the following steps: Step (1): adding glucose, anhydrous citric acid and 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole into deionized water, heating to 180-185° C. for reaction for 4-4.5 hours, cooling, vacuum filtering, purification and freeze drying to obtain a carbon dot corrosion inhibitor; Step (2): ultrasonically dispersing the carbon dot corrosion inhibitor in deionized water, adjusting the pH to 6-6.5; adding 1-ethyl-carbodiimide hydrochloride solution and N-hydroxysuccinimide solution to activate, adding dopamine, passing oxygen to remove dissolved oxygen in the reaction system, stirring the reaction for 3-3.5 hours, purifying, and vacuum drying to obtain a modified carbon dot corrosion inhibitor; Step (3): ultrasonically dispersing the modified carbon dot corrosion inhibitor and hexagonal boron nitride in an N,N-dimethylformamide aqueous solution, centrifuging, vacuum filtering the supernatant, purifying, and vacuum drying to obtain intercalated modified boron nitride nanosheets.

2. The process for preparing a corrosion-resistant galvanized steel pipe according to claim 1, characterized in that: In the carbon dot corrosion inhibitor, the mass ratio of glucose: anhydrous citric acid: 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole is 1:1:(0.5-1.2).

3. The process for preparing a corrosion-resistant galvanized steel pipe according to claim 1, characterized in that: In the modified carbon dot sustained-release agent, the mass ratio of carbon dot corrosion inhibitor to dopamine is 80:(60-75.9).

4. The process for preparing a corrosion-resistant galvanized steel pipe according to claim 1, characterized in that: In the intercalated modified boron nitride nanosheets, the mass ratio of modified carbon point corrosion inhibitor to hexagonal boron nitride is (0.25-0.5):0.

2.

5. The process for preparing a corrosion-resistant galvanized steel pipe according to claim 1, characterized in that: In the modified zinc oxide nanoparticles A, the mass ratio of zinc oxide nanoparticles: dopamine: corrosion inhibitor in the corrosion inhibitor solution is 2: (2-3): (8-9); in the modified zinc oxide nanoparticles B, the mass ratio of modified zinc oxide nanoparticles A: KH590 is (4-5): (1.6-3).

6. The process for preparing a corrosion-resistant galvanized steel pipe according to claim 1, characterized in that: In the composite boron nitride nanosheets, the mass ratio of intercalated modified boron nitride nanosheets to modified zinc oxide nanoparticles B is 3:(1-2).

7. The process for preparing a corrosion-resistant galvanized steel pipe according to claim 1, characterized in that: The components in the passivation solution are as follows, by weight: 0.5-0.8 parts of tannic acid, 0.15-0.2 parts of fatty alcohol polyoxyethylene ether, 0.15-0.2 parts of hydroxyethylidene diphosphonic acid, 0.15-0.2 parts of emulsifier, 40-50 parts of aqueous acrylic resin solution, and 1-5 parts of composite boron nitride nanosheets.

8. The process for preparing a corrosion-resistant galvanized steel pipe according to claim 1, characterized in that: The method for preparing the galvanized steel pipe comprises the following steps: The steel pipe substrate is sequentially subjected to degreasing, water washing, pickling, and water washing pretreatment; the pretreated steel pipe is placed in a chemical plating solution, heated to 50-55°C and subjected to constant temperature chemical galvanizing for 10-15 minutes to obtain a galvanized steel pipe; The solution used in the degreasing step is a 10wt% sodium hydroxide solution, and the solution used in the pickling step is a 16wt% hydrochloric acid solution; the chemical plating solution is composed of 30-40g / L zinc sulfate heptahydrate and 140-150g / L potassium pyrophosphate trihydrate; the thickness of the galvanized layer of the galvanized steel pipe is 8-9μm.

9. A corrosion-resistant galvanized steel pipe prepared according to the preparation process of a corrosion-resistant galvanized steel pipe according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Dual-modified waterborne epoxy resin anticorrosive paint and preparation method thereof

    CN113308174A

  • Polydopamine modified boron nitride nanosheet / polyimide heat-conducting insulating composite film as well as preparation method and application thereof

    CN114750491A

  • High-performance water-soluble semi-synthetic cutting fluid and preparation method thereof

    CN114940923A

  • Anti-corrosion grounding material and processing technology thereof

    CN115044291A

  • "brick-mortar" layered structure corrosion-resistant phosphate composite coating, and preparation method and use therefor

    WO2024056109A1